2015
DOI: 10.1016/j.nucmedbio.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of hIgG1-Fc to 111In-anti-amyloid single domain antibody fragment VHH-pa2H prolongs blood residential time in APP/PS1 mice but does not increase brain uptake

Abstract: Using VHH-Fc conjugates increases the blood half-life of the protein. However, purely extending the time window for brain uptake does not increase BBB passage. Nevertheless, VHH-Fc holds promise for therapeutic applications where a sustained systemic circulation of VHH is advantageous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 44 publications
0
35
0
1
Order By: Relevance
“…SdAbs can be readily fused to human Fc-domain to overcome the limitations of the monovalent sdAbs, such as the short blood residential time and lacking antibody-dependent cell-mediated cytotoxicity and complement dependent cytotoxicity 11 . In addition, bivalent sdAbs can be obtained via the disulfide bond formation in Fc hinge area, which was reported to significantly increase sdAb’s activity 12 .…”
Section: Resultsmentioning
confidence: 99%
“…SdAbs can be readily fused to human Fc-domain to overcome the limitations of the monovalent sdAbs, such as the short blood residential time and lacking antibody-dependent cell-mediated cytotoxicity and complement dependent cytotoxicity 11 . In addition, bivalent sdAbs can be obtained via the disulfide bond formation in Fc hinge area, which was reported to significantly increase sdAb’s activity 12 .…”
Section: Resultsmentioning
confidence: 99%
“…The results of a competitive ligand-binding assay suggested that 3F11 completely blocked the binding between SARS-CoV-2 RBD and ACE2. 29 To overcome the limitations of monovalent sdAbs, 30 sdAbs was fused with human IgG1 Fc fragments. Results showed that the neutralization activity of recombinant 3F11 significantly increased by 10.8-fold in molar concentration with an IC 50 value of 0.0020 µg/ml in a SARS-CoV-2 pseudotyped virus entry assay.…”
Section: Structure and Function Of The Rbd In Sars-cov And Sars-cov-2mentioning
confidence: 99%
“…31 Although several studies have also shown that several VHHs are able to penetrate into the brain in vivo, 28,29,45 BBB crossing by VHH remains highly variable. 30,63 Here, we show that R3VQ-S-(DOTA/Gd) 3 binds the Aß peptide with high specificity and sensitivity and labels amyloid deposits on brain section of a mouse model of amyloidosis. Furthermore, we demonstrated its ability to cross the BBB and to label amyloid deposits after intravenous injection in mice.…”
Section: R3vq-s-(dota/gd) 3 Imaging Probe Crosses the Bbb And Binds Tmentioning
confidence: 77%